2013
DOI: 10.1108/02640471311299146
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the awareness and ability of medical students in using electronic resources of the integrated digital library portal of Iran

Abstract: PurposeThe present paper aims to compare the awareness and ability of medical students in using the electronic resources of the Integrated Digital Library (IDL) portal of Iran.Design/methodology/approachThe current research involves a comparative applied survey. The survey was conducted through a structured questionnaire circulated among 300 medical students sampled from three major Iranian universities. A stratified random sampling method was used. Descriptive statistics (mean, standard deviation, average and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, for the effective use of electronic resources it is not enough to have a powerful computer and fast Internet access; it is also necessary to have specific knowledge and skills. Several studies show that students lack such competencies (Agboola, 2010;Boumarafi, 2010;Kahouei, Babamohamadi, Panahi, & Zadeh, 2013;Manda, 2005;Nemati Anaraki & Babalhavaeji, 2013;Yu-Mei & Artero, 2005), and that, despite the existing knowledge and skills, they need additional training (Baro & Fyneman, 2009;Harrington, 2009;Judd & Kennedy, 2011). Language barriers may also prevent students from using electronic resources (Shuling, 2007;Wu & Chen, 2012).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 96%
“…However, for the effective use of electronic resources it is not enough to have a powerful computer and fast Internet access; it is also necessary to have specific knowledge and skills. Several studies show that students lack such competencies (Agboola, 2010;Boumarafi, 2010;Kahouei, Babamohamadi, Panahi, & Zadeh, 2013;Manda, 2005;Nemati Anaraki & Babalhavaeji, 2013;Yu-Mei & Artero, 2005), and that, despite the existing knowledge and skills, they need additional training (Baro & Fyneman, 2009;Harrington, 2009;Judd & Kennedy, 2011). Language barriers may also prevent students from using electronic resources (Shuling, 2007;Wu & Chen, 2012).…”
Section: Students' Perceptions Of Electronic Resourcesmentioning
confidence: 96%
“…In contrast, the results of the present study showed the good speed of access to library websites and their pages. It should be noted that this discrepancy could be related to the speed of the Internet connection as well as communication infrastructure issues 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The above suggests that participants used their class WhatsApp accounts to develop mathematics discipline habits which are promoted through direct instructions, if learning intention is to achieve high marks (Dowling & Wilson, 2017). The direct instructions are used to indicate to students what exactly is missing, in order for the students to correct such, achieving one hundred per cent (Anaraki & Babalhavaeji, 2013;Khoza, 2020;Zaitun, 2010). An example of a direct instruction is that when a student writes X + 2X = X 2 , the lecturer will simply state: 'the answer is wrong', not putting this more sensitively.…”
Section: Instructions and Contentmentioning
confidence: 99%
“…WhatsApp has changed learning to social learning. Such has promoted social habits that help students to address societal needs, through new, group-developed skills (Anaraki & Babalhavaeji, 2013). Although socialization habits drive the learning, learning management systems (LMSs) such as Modular Object-Oriented Dynamic Learning Environment (Moodle) and others maintain and continue with the content-centred approach that promotes discipline habits, addressing discipline needs.…”
Section: Introductionmentioning
confidence: 99%